COVID-19-associated orphanhood and caregiver death in the United States - Hillis, SD; Blenkinsop, A; Villaveces, A; Annor, FB; Liburd, L; Massetti, GM; Demissie, Z; Mercy, JA; Nelson, CA; Cluver, L; Flaxman, S; Sherr, L; et al. (American Academy of Pediatrics, 2021)
Background: Most COVID-19 deaths occur among adults, not children, and attention has focused on mitigating COVID-19 burden among adults. However, a tragic consequence of adult deaths is that high numbers of children might lose their parents and caregivers to COVID-19-associated deaths.